Methionine and S-Adenosylmethionine Regulate Monascus Pigments Biosynthesis in Monascus purpureus - Yin, Sheng; Yang, Dongmei; Zhu, Yiying; Huang, Baozhu (Frontiers in Microbiology, 2022)
Amino acids metabolism could exert regulatory effects on Monascus pigments (MPs) biosynthesis. In this work, MPs biosynthesis regulated by methionine and S-adenosylmethionine (SAM) was investigated in Monascus purpureus RP2. The results indicated that addition of methionine in fermentation significantly reduced MPs production by 60~70%, and it induced a higher expression of SAM synthetase Mon2A2272 and consequently led to SAM accumulation. However, addition of SAM in fermentation obviously promoted MPs production by maximum 35%, while over-expression of gene Mon2A2272 led to a decrease in MPs yield, suggesting that SAM synthetase and SAM were likely to play different regulatory roles in MPs biosynthesis. Furthermore, gene transcription profile indicated that SAM synthetase expression led to a higher expression of the transcriptional regulatory protein of MPs biosynthesis gene cluster, while addition of SAM gave rise to a higher expression of MPs biosynthesis activator and the global regulator LaeA, which probably accounted for changes in MPs production and the mycelium colony morphology of M. purpureus RP2 triggered by methionine and SAM. In sum, this work proposed a possible regulation mechanism of MPs biosynthesis by SAM metabolism from methionine. The findings provided a new perspective for a deep understanding of MPs biosynthesis regulation in M. purpureus.